2021
DOI: 10.3889/oamjms.2021.6953
|View full text |Cite
|
Sign up to set email alerts
|

Shortage of Personal Protective Equipment and Nurse Safety in the Coronavirus Disease-19 Pandemic: A Cross-sectional Study in Indonesia

Abstract: BACKGROUND: There has been a substantial scarcity of personal protective equipment (PPE) in several countries during the ongoing pandemic of Coronavirus disease-19 (COVID-19). Nurses in Indonesia also experience a shortage of PPE as the number of COVID-19 patients in Indonesia continues to increase. There is no accurate data yet regarding the exact number of PPE scarcity for nurses. AIM: This study aimed to describe the availability of PPE and adverse consequences long-term used off the PPE and examine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, during the pandemic, hospitals experienced shortages of PPE (Cohen, Van Der & Rodgers 2020 ). This condition also found COVID-19 in Indonesia (Sampe et al 2021 ). The lack of PPE is one of the obstacles to adherence of IPC programme, which is often faced by hospitals in developing countries (Sharma et al 2015 ).…”
Section: Discussionsupporting
confidence: 67%
“…However, during the pandemic, hospitals experienced shortages of PPE (Cohen, Van Der & Rodgers 2020 ). This condition also found COVID-19 in Indonesia (Sampe et al 2021 ). The lack of PPE is one of the obstacles to adherence of IPC programme, which is often faced by hospitals in developing countries (Sharma et al 2015 ).…”
Section: Discussionsupporting
confidence: 67%
“…In Sampe et al ,[ 21 ] nurses complained about the lack of equipment, such as N95 masks, gloves, etc., Deldar et al . [ 22 ] reported that nursing managers, who had experience of caring for COVID-19 patients, mentioned the “lack of experienced and reliable staff” as one of their most important challenges.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of public panic stockpiling and a lower supply than demand, Indonesia, like most other countries, faced a scarcity of PPE at the start of the pandemic. [33][34][35] However, the situation has improved significantly, with most health facilities providing PPE to doctors and other healthcare employees.…”
Section: Discussionmentioning
confidence: 99%